Analysis of The Impact of The Region Expansion on Economic Growth (Case Study: Expansion of North Toraja Regency from Tana Toraja) - Tapparan, Samuel Randy; Wahab, Abdul (Universitas Negeri Makassar, 2019)
The increasing number of regions proposing themselves to form new autonomous regions since the enactment of Law Number 32 of 2004 concerning